Estimates of population-level palliative care need in the UK: a descriptive analysis of mortality data before and during the COVID-19 pandemic - Erin Raquel Fantoni; Natasha Wynne; Anne M. Finucane (BMC Palliative Care)
Abstract Background Existing estimates of palliative care need in the UK were produced before the COVID-19 pandemic. We sought to produce updated, population-level estimates of palliative care need for each of the four UK nations and explore how these changed during the pandemic. Methods We conducted a descriptive analysis of routine data. We used a well-established, diagnosis-based methodology which produced minimal estimates of palliative care need based on underlying causes of death; intermediate estimates based on underlying and contributory causes of death; and maximal estimates based on excluding unexpected causes of death. Additional estimates incorporated deaths involving COVID-19. All methods were applied to official mortality statistics from England, Wales, Scotland, and Northern Ireland for the years 2017 to 2021. Results From 2017 to 2019 for the UK in total, palliative care need was estimated at ~ 74% (minimal), ~ 90% (intermediate) and ~ 96% (maximal) of total deaths, which was broadly consistent with previous studies. Results were similar across all nations. In the pandemic years, 2020-21, the minimal estimates remained stable in terms of the number of people in need but dropped significantly in terms of the proportion of deaths associated with palliative care need (to ~ 66%) due to the overall increase in mortality and large number of deaths from COVID-19. The intermediate (~ 90%) and maximal (~ 96%) estimates showed an increase in the number of people in need but remained stable in proportion of deaths. When deaths involving COVID-19 were treated as deaths associated with palliative need, the minimal estimates increased to ~ 77% and intermediate estimates increased to ~ 92%. Conclusions In each of the UK’s nations, most people who die will have palliative care needs. Excluding deaths from COVID-19 in population-level estimates of palliative care need risks under-estimating true levels of need. Future studies which estimate population-level palliative care need should consider factoring in deaths from COVID-19.